Hubungan Antara Disiplin Belajar. Dengan.Hasil.Belajar.Siswa Pada Mata Pelajaran Al-Quran Hadist di MAN 3 Agam - Rohdi, Nur Ulfa; Rizal, Eka; Aprison, Wedra; Kamal, Muhiddinur (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The main finding this study is that there are students who are not very disciplined and disciplined students whose learning outcomes from studying the Qur'an are really poor. purpose of this study is to determine whether there is a significant correlation between the learning outcomes of Al-Qur'an Hadist in MAN 3 Agam and the learning discipline. Correlational research is the type of study, and quantitative research is the method employed. The two variables that make up the research variables are learning outcomes (Y) and learning discipline (X). 48 pupils from class XI MAN 3 Agam for the 20232024 academic year made up the study's population. Saturated samples were used for the sampling process. in order for the whole population to serve as the sample. Learning discipline questionnaires and student learning result documents are used in data collecting. The study's findings demonstrate a connection between students' learning outcomes in the Al-Qur'an Hadith course at MAN 3 Agam and their learning discipline. According to the statistical test, it has a positive association with a Pearson correlation of 0.750 and a significance value of 0.000 > 0.05. Ha is thus accepted but Ho is refused. This indicates a connection between Al-Qur'an Hadith course at MAN 3 Agam and student learning outcomes in terms of learning discipline.